2020
DOI: 10.25134/quagga.v13i1.3202
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Multimedia Interaktif Terintegrasi Nilai Sains Sebagai Solusi Peningkatan Kemampuan Berpikir Kritis Kelas XI Mata Pembelajaran Biologi Di Tingkat SMA/MA

Abstract: Abstrak: Pemanfaatan teknologi kurang direalisasikan padahal penggunaan media teknologi seperti multimedia interaktif android dapat menjadikan pembelajaran lebih efektif dan bermakna. Penelitian ini bertujuan untuk mengembangkan multimedia interaktif terintegrasi nilai sains yang dilihat dari segi kelayakan dan keefektifan multimedia interaktif terintegrasi nilai sains sebagai solusi peningkatan kemampuan berpikir kritis peserta didik. Metode penelitian Research and Development (R&D) Borg and Gall dengan 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Articles that do not meet the criteria are a lot because the research on the article was carried out before the covid-19 pandemic, and the level of education is not at high school or Madrasah Aliyah (SMA/MA). Darmawan & Nawawi, 2020;Haka, Majid, et al, 2021;Haka, Suryaasih, et al, 2021;Hariyadi, 2021;Irwandi & Lusilawat, 2021;Nurbaetina & Roviati, 2021;Putri & Ardi, 2021;Ramadan et al, 2021;Saraswati et al, 2021;Sriwiyati, 2021;Talakua & Elly, 2020;Utami et al, 2020;Wicaksana et al, 2020;Zulfarina et al, 2021) 16 National journal (Not accredited) (Kania et al, 2021;Liunsanda et al, 2021;Mahendra, 2021;Pawicara & Conilie, 2020;Prihatiningtyas et al, 2021;Riska et al, 2021) 6 Thesis (Dewi, 2021;Nurdayanti et al, 2021;Pamungkas, 2021;Syahpitri, 2021;Tandirerung, 2021) 5 Proceeding (Raneza et al, 2021) 1 Total 29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles that do not meet the criteria are a lot because the research on the article was carried out before the covid-19 pandemic, and the level of education is not at high school or Madrasah Aliyah (SMA/MA). Darmawan & Nawawi, 2020;Haka, Majid, et al, 2021;Haka, Suryaasih, et al, 2021;Hariyadi, 2021;Irwandi & Lusilawat, 2021;Nurbaetina & Roviati, 2021;Putri & Ardi, 2021;Ramadan et al, 2021;Saraswati et al, 2021;Sriwiyati, 2021;Talakua & Elly, 2020;Utami et al, 2020;Wicaksana et al, 2020;Zulfarina et al, 2021) 16 National journal (Not accredited) (Kania et al, 2021;Liunsanda et al, 2021;Mahendra, 2021;Pawicara & Conilie, 2020;Prihatiningtyas et al, 2021;Riska et al, 2021) 6 Thesis (Dewi, 2021;Nurdayanti et al, 2021;Pamungkas, 2021;Syahpitri, 2021;Tandirerung, 2021) 5 Proceeding (Raneza et al, 2021) 1 Total 29…”
Section: Resultsmentioning
confidence: 99%
“…(Haka, Suryaasih, et al, 2021) 1Human digestive system (Tandirerung, 2021; Zulfarina et al, 2021) 2 Human respiratory system(Irwandi & Lusilawat, 2021;Nurdayanti et al, 2021) 2 Human reproductive system(Saraswati et al, 2021) …”
mentioning
confidence: 99%
“…According to Nunung (2019), 81.9% of students responded positively to the SAVI-based learning module on ecosystem content. According to Haka et al (2020), The incorporation of science into the creation of interactive multimedia is regarded as highly viable. Based on the three relevant investigations, the researchers are able to determine the responses of MAS Subulussalam Sumberjo students to the use of multimedia in biology learning.…”
Section: Resultsmentioning
confidence: 99%
“…Nunung (2019) reported that student responses to SAVI-based learning modules (somatic, auditory, visualization, intelligence) on ecosystem materials at SMAN 1 explained. Haka et al (2020) asserted that development of interactive multimedia that integrates the value of science as a solution to improve critical thinking skills for class xi biology subjects at the high school level.…”
Section: A Introductionmentioning
confidence: 99%
“…According to Qumilaila [7], biological material can be seen as something simple, but it can also be seen as something complicated and complex. Based on the results of Haka's research and discussion [8], interactive multimedia integrated with scientific values are very suitable for use as a biology learning medium.…”
Section: Learning Outcomes Of Biologymentioning
confidence: 99%